Hydrolysis Rates of Different Small Interfering RNAs (siRNAs) by the RNA Silencing Promoter Complex, C3PO, Determines Their Regulation by Phospholipase Cβ - Sahu, Shriya (American Society for Biochemistry and Molecular Biology, 2014)
C3PO plays a key role in promoting RNA-induced gene silencing. C3PO consists of two subunits of the endonuclease translin-associated factor X (TRAX) and six subunits of the nucleotide-binding protein translin. We have found that TRAX binds strongly to phospholipase Cβ (PLCβ), which transmits G protein signals from many hormones and sensory inputs. The association between PLCβ and TRAX is thought to underlie the ability of PLCβ to reverse gene silencing by small interfering RNAs. However, this reversal only occurs for some genes (e.g. GAPDH and LDH) but not others (e.g. Hsp90 and cyclophilin A). To understand this specificity, we carried out studies using fluorescence-based methods. In cells, we find that PLCβ, TRAX, and their complexes are identically distributed through the cytosol suggesting that selectivity is not due to large scale sequestration of either the free or complexed proteins. Using purified proteins, we find that PLCβ binds ∼5-fold more weakly to translin than to TRAX but ∼2-fold more strongly to C3PO. PLCβ does not alter TRAX-translin assembly to C3PO, and brightness studies suggest one PLCβ binds to one C3PO octamer without a change in the number of TRAX/translin molecules suggesting that PLCβ binds to an external site. Functionally, we find that C3PO hydrolyzes siRNA(GAPDH) at a faster rate than siRNA(Hsp90). However, when PLCβ is bound to C3PO, the hydrolysis rate of siRNA(GAPDH) becomes comparable with siRNA(Hsp90). Our results show that the selectivity of PLCβ toward certain genes lies in the rate at which the RNA is hydrolyzed by C3PO.